PENGEMBANGAN DESA PERTANIAN CABAI DI DESA BONGKI LENGKESE KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Rikasari, Rikasari (POPULIKA, 2022)
The purpose of this research was to determine innovation in production development as well as supporting factors and inhibiting factors for chili production in Bongki Lengkese Village, East Sinjai District, Sinjai Regency. The type of this  research used qualitative descriptive approach.  The number of informants was 6 person. The technique of collecting data were by interviews, observation, library research, documentation. The results of this research indicated that the innovation of chili farmers in Bongki Lengkese Village, East Sinjai District, Sinjai Regency has been carried out by simultaneously planting chilies and a management system using a cultivator tool for making beds on chili plantations and has a supporting factor in the form of cooperation with the company PT Hextar Seed to procure seeds with  superior quality and affordable prices and also supported by the assistance of chili seeds from the Department of Agriculture.  The inhibiting factors of chili plantations are the limited tools in the maintenance process up to the harvesting process, the unstable marketing location and the unstable selling price of chilies.